Risk in homeopathy: Classification of adverse events and homeopathic aggravations – A cross sectional study among Norwegian homeopath patients. Issue 4 (August 2015) - Stub, Trine; Kristoffersen, Agnete E.; Alræk, Terje; Musial, Frauke; Steinsbekk, Aslak
Highlights This is the first study to apply criteria that distinguish homeopathic aggravations from adverse events when assessing patient reported worsening of symptoms during homeopathic treatment. The patients reported worsening of symptoms 14 days after taking homeopathic remedy was classified as mild or moderate suggesting that the risk connected to homeopathic treatment is minor. We recommend that similar studies are undertaken to test the validity of the criteria used in this study as further development and improvement are warranted.